Synthesis and in-vivo anti-convulsant activity of prodrug of 3-alkylglutamic acid in albino rats - Namdeo K.P.; Shrivastava S.K.; Chandra R. (My University, 2025)
3-Alkyl glutamic acid decrease excitation and glutamate in brain. 3-Alkyl glutamic acid analogues displayed glutamic acid decarboxylase activation activity and anticonvulsant activity. We herein are reporting the result of our studies on the synthesis and evaluation of anticonvulsant activity for prodrug of 3-Alkyl Glutamic Acid. Prodrugs of Glutamic Acid were synthesized by taking the Dihydropyridine compound as carrier molecules and were subjected to preliminary screening for anticonvulsant activity in albino rats. Anticonvulsant activity of all the compounds were tested by chemo- convulsion method and all the compounds were found to be active. All the compounds were also studied for oxidation in various biological fluids and were found to be stable. Oxidized form of the conjugate inside the brain act as prodrug, which on hydrolysis yields parent drug in sustained release pattern. The significance of the work is to treat neurological disorder implicated by Glutamate.